Analisis Kesulitan Siswa dalam Memecahkan MasalahGaris Singgung Lingkaran pada Siswa Kelas VIIIMTs Muhammadiyah Waru Baki SukoharjoTahun Ajaran 2015/2016 - Novitasari, ﻿Dwi, Dra. Nining Setyaningsih, M.Si, Sri Rejeki, M.Pd, M.Sc (2016)
The research aims to describe students difficulties in solving problem related tangent circle. The difficulties are viewed from the steps of polya method. This is a qualitative descriptive research. The subjects were 5 students of grade VIII C MTs Muhammadiyah Waru Baki Sukoharjo. The data collection was conducted using test, interviews, observation and dokumentation. The data analysis was conducted in three stages namely data reduction, data presentation and drawing conclusion. The analytical framework was developed based on polya steps. Polya method is a classification of the problem solving ability of students which consists of four phases namely understanding the problem, divising a plan, carrying out the plan and looking back. Based on the analysis, it can be concluded that students difficulties are mainly on carrying out the plan and looking back. While, students error are mainly on interpreting the formula and principle error using the formula. In general the factors causing difficulties experienced by student are 1) low omprehension ability of students, 2) student difficulties in reading on the subject matter, 3) weak memory of students in using formula, 4) student low ability in interpreting or entering data into the formula, 5) does not review or re-examine the answers. Keyword : tangent circles, learning difficulties, Polya method